Correlation between albumin creatinine ratio and hypertension in type 2 diabetes - Vitasari Indriani; Wahyu Siswandari; Pugud Samudro; Nor Sri Inayati (JHeS (Journal of Health Studies), 2020)
Hypertension is often found in patients with type 2 diabetes. Albumin Creatinine Ratio (ACR) is used to detect early symptoms of kidney disease in patients with type 2 diabetes. The aim of this study is to determine the correlation between ACR and hypertension, as well as its relationship with other risk factors in type diabetes patients 2. Data were collected from 112 diabetic patients at PROLANIS FKTP Banyumas to see ACR and blood pressure. The results showed that poor glycemic control could be one of the risk factors. It can be concluded that detecting kidney dysfunction through ACR and starting treatment as early as possible can avoid the worst possibilities in type 2 diabetes patients.